ЭТНОГРАФИЯЛЫҚ ЛЕКСИКАНЫҢ ТҮРКИЙ ТИЛЛЕРДЕ ИЗЕРТЛЕНИЎИ - Үсенова, Қ. (FAN va JAMIYAT, 2021)
This article is examined the level of studying the ethnographic lexicon in Turkic languages. The study of individual thematic groups of lexicon, the etymological basis of words were also discussed, the language of Turkic peoples, ethnocultural features in Turkic languages.